Islamic-Based Counseling Approaches for Student Mental Well-Being: A Systematic Literature Review - Suhertina, Suhertina (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
The mental health of Muslim students has become a critical issue that demands counseling approaches grounded in Islamic spiritual and cultural values. This study aims to conduct a systematic literature review on Islamic counseling approaches that support the mental health of Muslim students or adolescents, as well as to analyze their effectiveness and implementation challenges. The method employed is a systematic literature review of ten scholarly articles published in 2025, selected based on strict inclusion and exclusion criteria. The review findings indicate that Islamic counseling approaches are highly diverse, encompassing tazkiyatun nafs, sufi psychotherapy, Islamic Cognitive Behavioral Therapy (ICBT), Islamic expressive writing, Islamic character education, and innovations in sharia-based digital counseling services. Most of these approaches have proven effective in enhancing mental resilience, reducing anxiety, improving emotional balance, and strengthening students' spiritual resilience. Nevertheless, several challenges were identified, including the limited competence of Islamic counselors, social stigma against counseling services, technological barriers, and the lack of longitudinal evidence-based studies. This review highlights the importance of developing Islamic counseling services that are structured, empirically grounded, and supported by collaboration among practitioners, academics, and policymakers to promote the mental health of Muslim youth in the contemporary era.